Quality of life and family communication in teenage mothers - Bulnes Bedón, Mario (1999)
It presents a report on a research with a sample of 123 adolescent mothers from different hospitalary institutions of Lima. It assesses the relation degrees between life style, familiar communication and the adolescent mother condition variables.